ANALYSIS OF FACTORS ASSOCIATED WITH OWNERSHIP OF FAMILY LATRINES IN UJONG RIMBA COMMUNITY HEALTH CENTRE WORKING AREA, MUTIARA TIMUR DISTRICT, PIDIE REGENCY - Munawarah, Zakiya; Hermansyah, Hermansyah; Syarifuddin, Syarifuddin; Santi, Tahara Dilla (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2023)
Background: As many as 18.84% of households in Aceh Province do not have access to defecation facilities. Pidie Regencyrecorded that 66.3% of households did not have access to private defecation facilities/family latrines, and in the Ujong Rimba Community Health Center working area, reported 50.5% of families do not have family latrines. The aim of this research is to analyze factors related to family latrine ownership and use in the working area of the Ujong Rimba Health Center, Mutiara Timur District, Pidie Regency in 2020. Method: This research is descriptive analytical with a cross sectional approach. Sampling used simple random sampling, totaling 98 families. Determining the number of samples for each family is calculated using the proportional sampling formula. Data collection was carried out for 9 days from 21 to 29 February 2020 using questionnaires through interviews. Data analysis used the chi-square test with the SPSS computer program. Result The results showed that there was a significant relationship between latrine ownership and education (p=0.001), income (p=0.007), knowledge (p=0.001), attitudes (p=0.038), habits (p=0.001), community participation (p=0.010) and the role of community service officers (p=0.038). Recommendation: It is hoped that the community health center and related agencies can continue to provide encouragement and motivation for the community to be able to have a family toilet and be able to use the family toilet properly.